Transformasi Good Corporate Governance menjadi Islamic Corporate Governance dalam Ekonomi Syariah - Saleh, Muhammad; Irawan, Andhi; Bakar, Abu; Rahmaniah, Amelia; Umar, Masyitah (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2026)
The implementation of Good Corporate Governance (GCG) has become a crucial instrument in maintaining corporate sustainability in the era of globalization, including within the Islamic economic sector. This paper aims to analyze the transformation of conventional GCG principles into Islamic Corporate Governance (ICG) and its implementation in Islamic banking in Indonesia. GCG is generally based on five main principles: transparency, accountability, responsibility, independence, and fairness. However, in the Sharia context, corporate governance undergoes an expansion through a Tauhid and Shura-based approach, where accountability is not only directed toward stakeholders but also serves as a form of worship to Allah SWT (God-interest). The fundamental difference in ICG lies in the integration of Islamic values such as Shidiq, Tabligh, Amanah, and Fathonah, as well as the vital role of the Sharia Supervisory Board (DPS) to ensure compliance with the fatwas of the Indonesian Council of Ulama. The study indicates that the implementation of ICG through Financial Services Authority regulations and the Sharia Banking Law enhances credibility, mitigates agency risks, and guarantees the rights of all parties based on social justice. This transformation proves that ICG is not merely an adoption of Western models (Anglo-Saxon or European), but a unique value system that combines market efficiency with religious moral principles to achieve long-term collective welfare.